NÄ«shÄpÅ«rÄ« Scholars in The Formation of SunnÄ« Scholarship in The Eleventh Century - Widigdo, Mohammad Syifa Amin (Al-Jamiah: Journal of Islamic Studies, 2017)
The role of NÄ«shÄpÅ«rÄ« medieval scholars in the tenth-eleventh century in the formation of SunnÄ« orthodoxy has been rarely discussed. The existing scholarship focuses primarily on the local history of NÄ«shÄpÅ«r and other parts of eastern Muslim world or emphasizes more on the contribution of BaghdÄdÄ« scholars in the light of the formation of SunnÄ« legal schools, which in turn is deemed as SunnÄ« orthodoxy, than their counterpart in NÄ«shÄpÅ«r and other cities in the east. Therefore, this paper attempts to show how Muslim scholars from NÄ«shÄpÅ«r contributed to the advancement of SunnÄ« scholarship in the fifth/eleventh century through a closer study of intellectual strategies developed and employed by NÄ«shÄpÅ«rÄ« scholars to cope with their local challenges. They built intellectual networking and attempted to integrate legal and theological scholarship in Islamic scholarship to deal with their local problems, which interestingly shaped their distinctive contribution in the light of SunnÄ« scholarship tradition. By means of this attempt of intellectual networking and harmonizing legal scholarship (fiqh) and theological scholarship (kalÄm), they were not only able to tackle local problems but also equipped with intellectual means to push doctrinal boundaries within SunnÄ« scholarship in the fifth/eleventh century.[Peran ilmuwan NÄ«shÄpÅ«r abad pertengahan dalam pembentukan ortodoksi Sunni di abad 10 â 11 masehi masih jarang dibahas. Kebanyakan sarjana yang ada lebih banyak memperhatikan sejarah lokal NÄ«shÄpÅ«r dan bagian lain dari dunia muslim di timur atau menekankan pada kontribusi sarjana asal BaghdÄd dimasa puncak formasi mazhab Sunni, dimana lebih sering dianggap sebagai Sunni ortodoks daripada kawan mereka di NishÄpÅ«r dan kota lain di timur. Oleh karena itu, artikel ini berusaha untuk menunjukkan bahwa sarjana muslim dari NishÄpÅ«r berkontribusi pada pengembangan pemikiran Sunni di abad pertengahan melalui kajian mendalam pembangunan strategis intelektual dan karya dari sarjana NishÄpÅ«r dalam mengatasi tantangan lokal. Mereka membangun jaringan intelektual dan berusaha mengintegrasikan hukum dan teologi dalam Islam dengan masalah lokalitas, yang mana kontribusi khasnya berpengaruh dalam tradisi teologi Sunni. Melalui usahanya ini, jaringan intelektual dan harmonisasi fiqh dan kalam, mereka tidak hanya mengatasi persoalan lokal tetapi juga melengkapinya dengan seperangkat intelektual untuk mendorong batas-batas dalam tradisi Sunni di abad pertengahan.]Â  Â Â